1974
DOI: 10.1524/zpch.1974.92.4-6.354
|View full text |Cite
|
Sign up to set email alerts
|

A Neutron Diffraction Study of Prussian Blue,Fe4[Fe(CN)6]3·14D2O

Abstract: Since the early 18 th century1 the iron cyanide complex called Prussian Blue has repeatedly attracted the interest of chemists. The most striking feature of this classical coordination compound, the intense blue colour, is observed in neither of the components, Fe3+ and jFe(CiV)64_. This feature has instigated many investigations and speculations concerning its structure and bonding. Purthermore, Prussian Blue was very often used as a test substance when new

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The high temperature inverse susceptibility data recorded at 50 Oe (see Figure , inset) give a Weiss temperature of −12 K, suggesting that the dominant exchange interactions are antiferromagnetic. The effective magnetic moment per iron center is 5.7 μ B , which is close to the value of 5.9 μ B expected for the S = 5 / 2 ground-state associated with high-spin Fe III in an octahedral coordination environment and to the value for Prussian blue (5.8 μ B ) . It is well-known that Prussian blue shows ferromagnetic ordering at 5.6 K through a double-exchange mechanism that involves valence delocalization in the ground-state between Fe II and Fe III .…”
Section: Resultssupporting
confidence: 75%
“…The high temperature inverse susceptibility data recorded at 50 Oe (see Figure , inset) give a Weiss temperature of −12 K, suggesting that the dominant exchange interactions are antiferromagnetic. The effective magnetic moment per iron center is 5.7 μ B , which is close to the value of 5.9 μ B expected for the S = 5 / 2 ground-state associated with high-spin Fe III in an octahedral coordination environment and to the value for Prussian blue (5.8 μ B ) . It is well-known that Prussian blue shows ferromagnetic ordering at 5.6 K through a double-exchange mechanism that involves valence delocalization in the ground-state between Fe II and Fe III .…”
Section: Resultssupporting
confidence: 75%
“…Prussian blue is a mixed-valence cyanide-bridged cubic network containing low-spin Fe II (S ) 0) surrounded by carbon and high-spin Fe III (S ) 5 / 2 ) linked to the nitrogen atoms of the cyanide bridge. 7 It orders ferromagnetically below T C ) 5.6 K. 8 We have used our rational approach to prepare a discrete species that has the same local structure and electronic properties as Prussian blue. In a first report we have shown that the reaction of Fe III (salmeten)Cl with K 4 [Fe(CN) 6 ] leads to the formation of the heptanuclear compound [Fe II (CNFe III -(salmeten)) 6 ]Cl 2 ‚6H 2 O.…”
mentioning
confidence: 99%
“…Prussian blue is a mixed-valence cyanide-bridged cubic network containing low-spin Fe II ( S = 0) surrounded by carbon and high-spin Fe III ( S = 5 / 2 ) linked to the nitrogen atoms of the cyanide bridge . It orders ferromagnetically below T C = 5.6 K . We have used our rational approach to prepare a discrete species that has the same local structure and electronic properties as Prussian blue.…”
mentioning
confidence: 99%
“…This compound is famous because of its intense blue color, which arises from an intervalence band centered at 14 080 cm À1 associated with a charge transfer from the diamagnetic lowspin Fe II ion to the high-spin Fe III ion. [9] Another, maybe less well known, property of Prussian blue is the occurrence of ferromagnetic ordering below the Curie temperature (T C ) of 5.6 K. [10] Mayoh and Day proposed a model for the ferromagnetic exchange interaction based on a partial delocalization of the electrons occupying the Fe II t 2g orbitals on to the neighboring high-spin Fe III sites. [11] In order to gain more insights into the mechanism responsible for the ferromagnetic interaction we decided to use a molecular approach and prepare a discrete species that may reproduce the optical and the magnetic properties of Prussian blue.…”
mentioning
confidence: 99%